Sleep, circadian rhythms, and athletic performance. (October 2015) - Thun, Eirunn; Bjorvatn, Bjørn; Flo, Elisabeth; Harris, Anette; Pallesen, Ståle
Summary: Sleep deprivation and time of day are both known to influence performance. A growing body of research has focused on how sleep and circadian rhythms impact athletic performance. This review provides a systematic overview of this research. We searched three different databases for articles on these issues and inspected relevant reference lists. In all, 113 articles met our inclusion criteria. The most robust result is that athletic performance seems to be best in the evening around the time when the core body temperature typically is at its peak. Sleep deprivation was negatively associated with performance whereas sleep extension seems to improve performance. The effects of desynchronization of circadian rhythms depend on the local time at which performance occurs. The review includes a discussion of differences regarding types of skills involved as well as methodological issues.